The Effect of Decision-Making Styles on Emotional Security and Loneliness in Adolescents: Testing a Structural Equation Model - Rigi , Safieh; Khodarahmi, Shahnaz; Rashidi , Hadi; Ashtiani, Ashkan; Omidbakhsh, Mojgan (Iranian Journal of Neurodevelopmental Disorders, 2026)
Purpose: Objective: The present study aimed to explain the direct and indirect relationships between decision-making styles and emotional security and loneliness among adolescents using a structural equation modeling approach. Methods and Materials: This study employed a descriptive–correlational and cross-sectional design and utilized Structural Equation Modeling (SEM). The statistical population consisted of all adolescents aged 15–18 years who were students in Tehran between May and June 2024. The sample size included 200 participants selected through stratified random sampling. Research instruments included the Belonging and Emotional Security Tool (BEST), the General Decision Making Style Questionnaire (GDMS), and the UCLA Loneliness Questionnaire (Russell Loneliness Scale). Descriptive analyses were conducted using SPSS version 27, and structural equation modeling was performed using SmartPLS version 4. The significance level was set at 0.05. Findings: The results indicated that the avoidant decision-making style had a significant negative effect on emotional attachment (β = −0.421, T = 4.285, p < .001) and emotional security (β = −0.456, T = 4.015, p < .001), while showing a significant positive effect on loneliness (β = 0.253, T = 2.965, p = .003). In contrast, the dependent decision-making style showed no significant effect on emotional attachment (β = −0.037, p = .686), emotional security (β = −0.059, p = .450), or loneliness (β = 0.075, p = .343). Regarding the intuitive decision-making style, its effects on emotional attachment (β = −0.065, p = .443) and emotional security (β = 0.001, p = .993) were not significant; however, a significant positive effect on loneliness was observed (β = 0.212, T = 3.031, p = .002). The rational decision-making style demonstrated a significant positive effect on emotional attachment (β = 0.367, T = 6.927, p < .001) and emotional security (β = 0.121, T = 2.464, p = .014), along with a strong negative effect on loneliness (β = −0.462, T = 7.202, p < .001), confirming the determining role of this style within the proposed model. Conclusion: Overall, the findings indicate that decision-making styles play a decisive role in shaping emotional security and the experience of loneliness among adolescents. The rational style functions as a protective factor, whereas the avoidant style operates as a risk factor.